Electro-bioremediation of a mixture of structurally different contaminants of emerging concern - Guedes, Paula (2021)
(SOE2/P5/F0505) UIDB/04085/2020 UIDB/04612/2020 UIDP/04612/2020 SFRH/BPD/114660/2016 CEECIND/04210/2017)